Concomitance of monosomal karyotype with at least 5 chromosomal abnormalities is associated with dismal treatment outcome of AML patients with complex karyotype – retrospective analysis of Polish Adult Leukemia Group (PALG). Issue 4 (3rd April 2017) - Wierzbowska, Agnieszka; Wawrzyniak, Ewa; Siemieniuk-Rys, Monika; Kotkowska, Aleksandra; Pluta, Agnieszka; Golos, Aleksandra; Robak, Tadeusz; Szarawarska, Marta; Jaskowiec, Anna; Duszenko, Ewa; Rybka, Justyna; Holojda, Jadwiga; et al.
Abstract: Monosomal karyotype (MK) and complex karyotype (CK) are poor prognostic factors in acute myeloid leukemia (AML). A comprehensive analysis of cytogenetic and clinical factors influencing an outcome of AML-CK + was performed. The impact of cladribine containing induction on treatment results was also evaluated. We analyzed 125 patients with AML-CK + treated within PALG protocols. MK was found in 75 (60%) individuals. The overall complete remission (CR) rate of 66 intensively treated patients was 62% vs. 28% in CK + MK − and CK + MK + group ( p = .01). No difference in CR rate was observed between DA and DAC arms. The overall survival (OS) in intensively treated patients was negatively influenced by MK, karyotype complexity (≥5 abnormalities), and WBC >20 G/L in multivariate analysis. The addition of cladribine to DA regimen improved OS only in MK − but not in MK + group. In conclusion, concomitance of MK with ≥5 chromosomal abnormalities is associated with dismal treatment outcome in AMK-CK + .